Formulation, characterisation, and optimization of emulsion fuel - Muhammad Hashrul Tahpiz, Ibrahim (2015)
Emulsion is a mixture of two immiscible substances. For the emulsion, we have two types which are Oil-in water emulsions (O/W) and Water –in-oil emulsions (W/O). Diesel fuel emulsions are blended mixtures of diesel fuel, water, emulsifying agents and other additives, that reduce particulate matter (PM), oxides of nitrogen ( NOx) emissions, as a result of the added water. Addition of water to the emulsified fuel also reduces the energy content of the fuel, with corresponding reductions in fuel economy and engine power. Emulsified diesel fuel has been the subject of several studies, and for comparative purposes in several others. This emulsified diesel fuel is a combination of diesel fuel with 20% water by weight, and an "additive package" for stabilizing the fuel-water emulsion. To mixed diesel with water we should add surfactants. The surfactants that we used are Sorbitan monoolate, NF,(Span 80), Polysorbate 60,NF,(Tween 60), Polysorbate 80,NF,(Tween 80), Triton X-100. The components required for making emulsion are mechanical agitator, diesel, distillated water,surfactants, burette, and pipette.